Use of social media for informal language learning by Malaysian university students - Afendi Hamat; Haslinda Abu Hassan (Penerbit Universiti Kebangsaan Malaysia, 2019)
Social networking services (SNSs) are a much-touted technology for improved learning, yet very little research goes beyond the classroom-level controlled application of SNSs. This paper provides a look at reported usage and application of SNSs beyond the classroom, where data is scarce. The paper describes an investigation on whether Malaysian university students think SNSs are helpful for learning English, and the areas of language proficiency that these students perceived to benefit the most from their usage of SNSs. A total of 6,085 students participated in the online survey. Results indicate that an overwhelming majority (99.7%) make use of SNSs to learn English outside the classroom and 97.4% of these believe their use of SNSs helps improve their proficiency. The respondents indicated that the areas of proficiency that benefitted the most from their use of SNSs are writing, communication, vocabulary development and reading. In contrast, grammar as well as listening and speaking benefitted the least. The results presented a much needed, and currently lacking, view into the actual utility and use of SNSs for the purpose of informal learning of English among students in Malaysian universities.